EVALUATION OF METABOLIC SYNDROME AND ITS CLINICAL COMPONENTS IN A RURAL ADULT POPULATION (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Metabolic syndrome is a cluster of metabolic abnormalities including central obesity, hypertension, dyslipidemia, and hyperglycemia that significantly increase the risk of cardiovascular disease and type 2 diabetes mellitus. The prevalence of metabolic syndrome is increasing in rural populations due to changing lifestyle patterns and reduced physical activity. This study aimed to determine the prevalence of metabolic syndrome and its components among adults in a rural community. Methodology: This community-based cross-sectional study was conducted in the Department of General Medicine at Sree Mookambika Institute of Medical Sciences from January 2024 to October 2025. A total of 250 adults aged 18 years and above were selected using multistage random sampling technique. Data regarding demographic characteristics, lifestyle factors, anthropometric measurements, blood pressure, fasting blood glucose, and lipid profile were collected using a structured questionnaire and standardized procedures. Statistical analysis was performed using SPSS version 25.0, and p